Strategi Penggunaan Media Digital dalam Pengembangan Kurikulum PAK untuk Meningkatkan Partisipasi Siswa - Oktavianus Rangga; Dyulius Thomas Bilo (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Previous research shows that digital learning media can increase student learning motivation, facilitate interaction between teachers and students, and encourage educational innovation. Student participation in the learning process is a key factor in improving the quality of learning. In the context of PAK, student participation can be measured through their level of involvement in discussions, assignments and other activities related to the lesson material. In this paper, the method applied by the author is a qualitative descriptive method with a focus on literature study. where books and other literature are the main focus of his research. Teachers play an important role in integrating digital media in the development of the PAK curriculum. Digital media technology that can be used in developing the Christian Religious Education (PAK) curriculum includes various types of tools and platforms that can improve the quality of learning. The use of digital media in developing the PAK curriculum has shown a significant increase in student participation. Canva is a graphic design tool that allows users to design creative designs online. This is a graphic design platform that can be used to create various types of graphics for social media, presentations, posters, documents and other visual content. Guru also makes it easy to create teaching materials and create Bible text games or create Bible verse quizzes. Even though there are several weaknesses that must be taken into account, this is not a problem that cannot be resolved by presenting material interactively and responsively. Therefore, the use of information technology or digital media is very influential in improving the quality of student learning.